An Analysis of Multiple Predecessor Rain Events ahead of Tropical Cyclones Ike and Lowell: 10–15 September 2008 - Bosart, Lance F.; Cordeira, Jason M.; Galarneau, Thomas J. Jr.; Moore, Benjamin J.; Archambault, Heather M. (2012)
The article of record as published may be found at http://dx.doi.org/10.1175/MWR-D-11-00163.1 An analysis of three predecessor rain events (PREs) that occurred ahead of North Atlantic tropical cyclone (TC) Ike and east Pacific TC Lowell during 10–15 September 2008 is presented. The three PREs produced all-time daily record rainfall at many locations, including Lubbock, Texas (189.5 mm); Wichita, Kansas (262 mm); and Chicago–O’Hare, Illinois (169 mm), on 11–13 September, respectively. PRE 1 organized over Texas on 10 September with moisture from a stalled frontal boundary and the Bay of Campeche, and matured with moisture from TC Lowell. PRE 2 organized over the Texas Panhandle on 11 September with moisture from the Bay of Campeche, and developed and matured over Kansas and Missouri with moisture from TC Lowell. PRE 3 developed over Texas on 11 September, merged with and absorbed PRE 2 over Kansas and Missouri, and matured as it ingested moisture from TC Ike. All three PREs matured in the equatorward entrance region of an intensifying subtropical jet stream (STJ). Heavy rainfall with the three PREs occurred along a plume of moist air characterized by high precipitable water values that extended poleward over the central United States near the juxtaposition of the nose of a low-level jet, a region of lower-tropospheric forcing for ascent along a surface baroclinic zone, and the STJ equatorward entrance region. The cumulative upscale effect of persistent deep convection from the three PREs enhanced and “locked in” a favorable upper-tropospheric flow pattern conducive to ridge development over the Ohio Valley and STJ intensification over the central U.S. and Great Lakes region. NSF Grant ATM- 0849491 NOAA/CSTAR Grant NA07NWS4680001